Metastatic castration-resistant prostate cancer: Academic insights and perspectives through bibliometric analysis. Issue 15 (April 2020) - He, Lugeng; Fang, Hui; Chen, Chao; Wu, Yanqi; Wang, Yuyong; Ge, Hongwei; Wang, Lili; Wan, Yuehua; He, Huadong
Abstract: Background: In recent years, metastatic castration-resistant prostate cancer (MCRPC) and studies related to MCRPC have drawn global attention. The main objective of this bibliometric study was to provide an overview of MCRPC, explore clusters and trends in research and investigate the future direction of MCRPC research. Methods: A total of 4089 publications published between 1979 and 2018 were retrieved from the Web of Science (WoS) Core Collection database. Different aspects of MCRPC research, including the countries/territories, institutions, journals, authors, research areas, funding agencies and author keywords, were analyzed. Results: The number of annual MCRPC publications increased rapidly after 2010. American researchers played a vital role in this increase, as they published the most publications. The most productive institution was Memorial Sloan Kettering Cancer Center. De Bono, JS (the United Kingdom [UK]) and Scher, HI (the United States of America [USA]) were the two most productive authors. The National Institutes of Health (NIH) funded the largest number of published papers. Analyses of keywords suggested that therapies (abiraterone, enzalutamide, etc.) would attract global attention after US Food and Drug Administration (FDA) approval. Conclusions: Developed countries, especially the USA, were the leading nations for MCRPC research because of their abundant funding and frequent international collaborations. Therapy was one of the most vital aspects of MCRPC research. Therapies targeting DNA repair or the androgen receptor (AR) signing pathway and new therapies especially prostate-specific membrane antigen (PSMA)-based radioligand therapy (RLT) would be the next focus of MCRPC research.